2001
DOI: 10.1038/sj.ejcn.1601233
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of glycated haemoglobin in the general population: associations with diet, alcohol and cigarette smoking

Abstract: Objective: We evaluated cigarette smoking, alcohol intake and consumption of different foods as determinants of glycated haemoglobin in a general population sample. Design: Cross-sectional survey. Setting: England. Subjects: Representative sample of 15 809 adults aged 16 y and older. Data analysed for 9772 non-diabetic, white European subjects. Main outcome measures: Glycated haemoglobin (GHb). Analyses were adjusted for age, sex, body mass index (BMI), waist ± hip circumference ratio, activity level, and educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 52 publications
5
32
3
Order By: Relevance
“…This finding agrees with the findings of an inverse relationship between alcohol intake and hemoglobin A1C in previous studies using general populations 30,31) . However, the amount of alcohol intake is recommended to be less than 20-30 g ethanol per day from the viewpoint of prevention of hypertension 21) , and this amount corresponds to the alcohol intake of light drinkers in the present study.…”
Section: A B C D E Fsupporting
confidence: 83%
“…This finding agrees with the findings of an inverse relationship between alcohol intake and hemoglobin A1C in previous studies using general populations 30,31) . However, the amount of alcohol intake is recommended to be less than 20-30 g ethanol per day from the viewpoint of prevention of hypertension 21) , and this amount corresponds to the alcohol intake of light drinkers in the present study.…”
Section: A B C D E Fsupporting
confidence: 83%
“…This finding was in line with the study conducted in India [18]. Other studies also found a significant relationship in age categories, smoking, duration of diabetes [20][21][22] and male gender [18], however, our study did not bring any significant values in the latter three. The mean FBG of three month consecutive measure in our study was 168.69 (SD=71.37) mg/dl and it was again similar to the study conducted in Ethiopia [19].…”
Section: Discussioncontrasting
confidence: 36%
“…But, other studies reported the presence of association between HTN and glycemic control [14,18]. Still other studies shown that, smoking [21] and duration of diabetes [22] could result in major adverse events in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 89%
“…Among people without diabetes, moderate alcohol consumption may enhance insulin sensitivity [43][44][45][46][47][48][49][50][51] and has been shown to decrease A1C. [52][53][54][55][56] It is plausible that regular, moderate alcohol consumption by people with diabetes similarly enhances insulin sensitivity and improves glycemic control. If this is the case, it might follow that the effect would be greater among type 2 diabetes patients, as they typically have much greater insulin resistance than those with type 1 diabetes; we did not, however, find different patterns of effect by diabetes type in our cohort.…”
Section: Discussionmentioning
confidence: 99%